Sterols from the sponge Haliclona varia. - Hai Yen, Duong Thi; Thung, Do Cong; Thuy Hang, Dan Thi; Tuan Anh, Hoang Le; Nhiem, Nguyen Xuan; Dung, Duong Thi; Giang, Phan Minh; Tai, Bui Huu; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2016)
Using combined chromatographic methods, four sterols, 3β-hydroxycholest-5-en-7-one (1), 22(E)-3β-hydroxycholesta-5,22-dien-7-one (2), 3β,7α-dihydroxycholest-5-ene (3), and 3β,7β-dihydroxycholest-5-ene (4) were isolated from the methanol extract of the sponge Haliclona varia. Their structures were elucidated by 1D and 2D-NMR spectroscopic methods as well as in comparison with the previous literature. Compounds 2-4 were reported from the genus Haliclona for the first time. Keywords. Haliclona varia, sponge, sterol.